Serat Fiber Kelapa Sawit Sebagai Bahan Dasar Komposit Untuk Digunakan Sebagai Bahan Peredam Suara - Aritonang, Sovian; Rasendriya, Anselmo; Murniati, Riri (Rekayasa Material, Manufaktur dan Energi, 2024)
This research discusses the use of oil palm fiber as a base material for composites intended for sound insulation purposes. Sound insulation materials play a key role in reducing noise levels in various environments. Oil palm fiber is identified as a promising material for the effective and sustainable production of sound insulation materials. Test results indicate that the composite of oil palm husk demonstrates the highest sound absorption coefficient (α) at both standard and high frequencies. Consequently, the fiber from oil palm empty fruit bunches (EFB) can be utilized as a viable material for sound insulation composites, and further research can be conducted on the fiber materials from oil palm empty fruit bunches (EFB).